2018
DOI: 10.1002/jhet.3169
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of the Anticancer Properties of Novel Quinone Bearing Carbamyl β‐Lactam Hybrids

Abstract: This paper describes a simple and practical protocol for the direct synthesis of a series of new hybrid molecules of carbamyl β‐lactam derivatives bearing quinone moiety via [2 + 2] cycloaddition of Staudinger reaction. The β‐lactam ring is tolerating carbamylation and further leads to a variety of quinone hybrid derivatives. The structures of the compounds were characterized by IR, MS, nuclear magnetic resonance, and high‐resolution mass spectra analysis. All the new synthesized compounds were screened for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…Out of the 14 quinone bearing carbamyl-lactam-lactam hybrids synthesized, compound 79 exhibited excellent anticancer activity against the B16F10 cell line. However, the experiments also revealed that the carbamyl derivative with a methyl group at the piperidine rings on the 4-position displayed better activity with IC 50 value 24.40 μM [ 202 ]. Ranjbari S. et al (2020) synthesized beta-lactam-based heterocyclic derivatives and evaluated their anticancer activity on four representative cell lines.…”
Section: Current Advances In Nitrogen Containing Heterocycles As Anti...mentioning
confidence: 99%
“…Out of the 14 quinone bearing carbamyl-lactam-lactam hybrids synthesized, compound 79 exhibited excellent anticancer activity against the B16F10 cell line. However, the experiments also revealed that the carbamyl derivative with a methyl group at the piperidine rings on the 4-position displayed better activity with IC 50 value 24.40 μM [ 202 ]. Ranjbari S. et al (2020) synthesized beta-lactam-based heterocyclic derivatives and evaluated their anticancer activity on four representative cell lines.…”
Section: Current Advances In Nitrogen Containing Heterocycles As Anti...mentioning
confidence: 99%
“…Por su parte, los taninos son compuestos polifenólicos a los que se les ha reconocido propiedades antitumorales, antimutagénicos, antidiabéticos, antioxidante y antibióticos, por lo que la presencia de estos compuestos puede favorecer la vida útil de alimentos, al ser utilizados como aditivos [25]. Las cumarinas son benzopironas que permiten modificar edemas, igualmente se le reconocen propiedades antiarrítmicas, antisépticas, analgésicas, antioxidantes e inclusive anticoagulantes, dependiendo en gran medida del tipo de cumarina presente [2,26,27]. De otra parte, se ha relacionado la actividad anticancerígena, inmunomoduladora, antiinflamatoria, hipoglucemiante, hipolipemiante y hepatoprotectoras a la presencia de triterpenos, compuestos muy abundantes en el reino vegetal, estos son compuestos lipídicos no saponificables que se forman por la unión de isoprenos.…”
Section: Análisis De Tamizaje Fitoquímicounclassified